SMYD Proteins: Key Regulators in Skeletal and Cardiac Muscle Development and Function. Issue 9 (September 2014) - Du, Shao Jun; Tan, Xungang; Zhang, Jianshe
ABSTRACT Muscle fibers are composed of myofibrils, one of the most highly ordered macromolecular assemblies in cells. Recent studies demonstrate that members of the Smyd family play critical roles in myofibril assembly of skeletal and cardiac muscle during development. The Smyd family consists of five members including Smyd1, Smyd2, Smyd3, Smyd4, and Smyd5. They share two highly conserved structural and functional domains, namely the SET and MYND domains involved in lysine methylation and protein‐protein interaction, respectively. Smyd1 is specifically expressed in muscle cells under the regulation of myogenic transcriptional factors of the MyoD and Mef2 families and the serum responsive factor. Loss of function studies reveal that Smyd1 is required for cardiomyogenesis and sarcomere assembly in skeletal and cardiac muscles. Smyd2, on another hand, is dispensable for heart development in mice. However, Smyd2 appears to play a role in myofilament organization in both skeletal and cardiac muscles via Hsp90 methylation. A Drosophila Smyd4 homologue is a muscle‐specific transcriptional modulator involved in the development or function of adult muscle. The molecular mechanisms by which Smyd family proteins function in muscle cells are not well understood. It has been suggested that members of the Smyd family may use multiple mechanisms to control muscle development and cell differentiation, including transcriptional regulation, epigenetic regulation via histone methylation, and methylation of proteins other than histones, such as molecular chaperone Hsp90. Anat Rec, 297:1650–1662, 2014. © 2014 Wiley Periodicals, Inc.